Staff-less libraries : innovative staff design - Johannsen, Carl Gustav (Cambridge Chandus, 2017)
Staff-less public libraries, enabled by the newest technological developments, represent a significant and innovative aspect of the development of public libraries. Most important, the concept makes it possible radically to enlarge the availability of the users' access to the physical library up to 80-100 hours per week -- a significant step toward 24/7 library access. The ultimate aim of this book is to discuss the challenges, the pros and cons of this new library model based upon international experiences, and best practice cases. Also sociological concepts like social capital and trust will be included to explain the remarkable absence of vandalism in the open, staff-less libraries. The staff-less model was developed in two different corners of the world: the Far East and in the Nordic countries around 2002-2004. The concept is now being spread to many other countries. The book systematically draws upon the latest research, user surveys, library experiences and inputs from software developers"--
Keywords: Library personnel management; Public libraries -- Automation